Exploring the Potential of a Rights-Based Approach to Work and Social Inclusion for People with Lived Experience of Mental Illness in Ghana - Ursula M. Read; Lionel Sakyi; Wendy Abbey (Harvard FXB Center for Health and Human Rights, 2020)
Much of the focus on human rights and mental health in low- and middle-income countries (LMICs) has been on protection from coercion and abuse and on expanding access to mental health services, rather than on promoting and protecting social and economic rights. Despite the importance of work for mental health, there has been very limited consideration of the relationship between work and mental health in LMICs. This paper draws on ethnographic and participatory research in urban and rural sites in Ghana to illustrate the meanings and value of work, as well as experiences of support, exclusion, and discrimination, among people with lived experience of mental illness in Ghana. The paper outlines the policy context of mental health and human rights in Ghana and evaluates the challenges of implementing mental health, disability, and labor legislation to protect the rights of persons with mental illness-particularly the poorest and most vulnerable-in both formal and informal employment. The paper closes by discussing the potential of practices of solidarity and social activism to promote the rights of people with mental illness and push for change.